Relationship between high performance and sprint ability in elite long-distance runners - Yamanaka, R.; Ohnuma, H.; Tanji, F.; Ando, R.; Suzuki, Y. (The Journal of Physical Fitness and Sports Medicine, 2018)
[Aims] In general, increases in maximal oxygen uptake and lactate acid metabolism contribute to the improvement in the performance of long-distance runners. However, some previous studies have suggested that long-distance runners should have the ability to maintain high running velocity and exert on sprints during competitions. We therefore determined the relationship between the performance and the sprint ability of elite long-distance runners in the present study. [Methods] The subjects were 28 Japanese elite long-distance runners. The average personal best time for 5,000-m is 13:47 ± 0:17 s. We defined the 5,000-m personal time as the performance index for a long-distance runner. We measured the 100-m and 400-m sprint times as the indices of sprint ability. We also measured the standing broad jump and the standing five steps jump as the indices of leg power ability related to sprint ability. [Results] There were significant correlations between the 5,000-m personal best time and 100- m sprint time, on one hand, and that and 400-m sprint time, on the other hand. There were significant correlations between the 5,000-m personal best time and standing broad jump, on one hand, and that and standing five steps jump, on the other hand. [Conclusion] We suggested the possibility that it is more important element for elite long-distance runners to have high sprint ability than it has been considered.